Recent policies for financial market integration in Indonesia - Friedrich L. Sell (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1987)
In most developing countries financial markets are still highly fragmented and dualistic (Nunnenkamp 1985, p. 20). This is considered as a hindering factor to economic development. The rationale behind this is the view shared by most economists that a higher level of financial integration c.p. lowers intermediation costs, encourages competition and improves the allocation of loanable funds throughout the economy.
Keywords: 330